Case study of Dill's restaurant / Muhammad Afiq Abd … [et al.] - ABD HAMID, MUHAMMAD AFIQ; MOHAMED, HADI FAIZ; YUSOFF ABAS, SYARIFAH RYSMALIA MAYA; MAT MUKTI, NURUL SYAFIQA IZYAN; MOHAMED KHALID, SITI NUR HANIS (2018)
Dill's Restaurant was established in 15 November 2017 and company registered as a local SME company. The founder of this company is Ahmad Fadhil Bin Ramlan, 23 years old. Hence, the name of Dill's restaurant initially taken from his name. This restaurant serve variety type of western food such as chicken chop, lamb chop, meatballs and many more. Although his background study is in mechanical and certified in Diploma in Mechanical Engineering, he is not afraid and interested to try new major such as this business. Initially, he is interested to sell 'nasi kerabu' and had open a small stall located at Puchong. However, the feedback was not good and he decides to close the stall. He went back to his hometown and learn to make a good western food as this type of food is simpler to make and does not required any specific skills. He decide to give himself another try on this business, therefore he went back and opened a restaurant with his partner in 2016 under name 'TipTop' Restaurant. This restaurant located in Taman Putra Perdana, Puchong and serve variety type of western food. In the end of 2017, he decided to open anew branch at Padang Jawa, Shah Alam because he wanted to open his new company without a partnership. Furthermore, his target market is more to students, that is one of the reasons why Padang Jawa. Shah Alam is a strategic place to open a restaurant with an affordable price. During initial stage, the capital used to start up this business is around 50K with 4 workers. Meanwhile, after operates a few months the number of workers have been increase to 10 people..